Legal Analysis of Consumer Protection in the Application of SNI in Batam Free Trade Zone - Herlina Herlina; Tantimin Tantimin; Nurlaily Nurlaily (Fakultas Hukum Universitas Wahid Hasyim, 2026)
This study aims to analyse the regulation of the Indonesian National Standard (SNI) under Law Number 8 of 1999 concerning Consumer Protection and its implications for consumer protection in Batam City as a Free Trade Zone. The study is grounded in the discrepancy between das sollen and das sein, in which the prevailing legal framework obliges business actors to comply with SNI requirements, whereas in practice the implementation of SNI in Batam remains ineffective due to high certification costs, limited legal awareness among business actors, and the distinctive characteristics of the Free Trade Zone. This research employs a normative juridical method with statutory and case approaches, utilising primary, secondary, and tertiary legal materials. The findings demonstrate that Article 8 paragraph (1) and Article 4 letter (c) of Law Number 8 of 1999 impose an obligation upon business actors to implement SNI standards, while Article 19 paragraphs (1) and (2) provide consumers with the right to seek compensation for damages, and Article 45 paragraph (1) regulates the mechanism for dispute resolution through the Consumer Dispute Settlement Agency (BPSK). Nevertheless, normative inconsistencies between Law Number 39 of 2009 concerning Special Economic Zones and other related regulations have created obstacles to the implementation of SNI in Batam. Despite these challenges, the enforcement of SNI remains a legal obligation for business actors in order to ensure consumer protection, legal certainty, and the enhancement of trade quality within the free trade zone.